A Comparison of Visual Outcomes and Patient Satisfaction Between Photorefractive Keratectomy and Femtosecond Laser-Assisted In Situ Keratomileusis - Hashmani, Nauman (Cureus, 2017)
Purpose To compare visual outcomes and satisfaction among patients of photorefractive keratectomy (PRK; Wavelight EX 500, Alcon, Ft Worth, TX, USA) and femtosecond laser-assisted in situ keratomileusis (FAL; Wavelight FS 200 laser and Wavelight EX 500, Alcon, Ft Worth, TX, USA). Methods We performed a retrospective study of 409 eyes in 207 patients that underwent either PRK (n=90) or FAL (n=117) at the two centers of Hashmanis Hospital, Karachi, Pakistan. The included refractive outcomes were sphere diopters (D), cylinder D, and spherical equivalent D. Additionally, visual acuities were included. All of these were assessed preoperatively and at the one-month postoperative check-up. Patient satisfaction was gauged at the time of chart review by contacting the patient. Results When looking at the postoperative outcomes, we found all values to be statistically significant (p<0.001) with superior outcomes in the FAL cohort. Additionally, 90% and 15% of eyes achieved a postoperative uncorrected visual acuity (UCVA) of 20/20 in FAL and PRK, respectively. Furthermore, the efficacy indexes of the FAL and PRK arms were 1.00 and 0.82, respectively. The predictability of the procedures were 92.1% and 64.9%, respectively. Lastly, 93.3% of patients were satisfied with FAL and 95.7% with PRK. Conclusion Our study shows superior visual outcomes in patients undergoing FAL. However, we found a higher satisfaction rate in those that underwent PRK, perhaps due to the higher cost of FAL.